Human SLFN5 and its Xenopus Laevis ortholog regulate entry into mitosis and oocyte meiotic resumption - Vit, Gianmatteo; Hirth, Alexander; Neugebauer, Nicolas; Kraft, Bianca; Sigismondo, Gianluca; Cazzola, Anna; Teßmer, Claudia; Duro, Joana; Krijgsveld, Jeroen; Hofmann, Ilse; Berger, Michael; Klüter, Harald; et al. (Cell death discovery, 2022)
The Schlafen gene family was first described in mice as a regulator of thymocyte development. Further studies showed involvement of human orthologs in different processes related with viral replication, cellular proliferation, and differentiation. In recent years, a new role for human Slfn11 in DNA replication and chromatin remodeling was described. As commonly observed in many gene families, Slfn paralogs show a tissue-specific expression. This made it difficult to reach conclusions which can be valid in different biological models regarding the function of the different Schlafen proteins. In the present study, we investigate the involvement of SLFN5 in cell-cycle regulation and cell proliferation. A careful analysis of SLFN5 expression revealed that SLFN5 is highly expressed in proliferating tissues and that the protein is ubiquitously present in all the tissues and cell line models we analyzed. Very interestingly, SLFN5 expression oscillates during cell cycle, peaking during S phase. The fact that SLFN5 interacts with protein phosphatase 2A and that SLFN5 depletion causes cell cycle arrest and cellular apoptosis, suggests a direct involvement of this human paralog in cell cycle progression and cellular proliferation. We substantiated our in vitro and in cellulo results using Xenopus laevis oocytes to show that mRNA depletion of the unique Slfn gene present in Xenopus, whose protein sequence shares 80% of homology with SLFN5, recapitulates the phenotype observed in human cells preventing the resumption of meiosis during oocyte development.
Gesehen am 15.02.2023